GENETIC VARIABILITY AND HERITABILITY ESTIMATES FOR YIELD ATTRIBUTES AND LEAF RUST RESISTANCE IN F3 POPULATION OF WHEAT (TRITICUM AESTIVUM L.) - ARATI YADAWAD, R. R HANCHINAL, H. L. NADAF, S. A. DESAI, SUMA BIRADAR V. RUDRA NAIK (The Bioscan, 2015)
Fifty nine F3 lines of cross DWR162 X PBW343 subjected to study the genetic variability for grain yield, its attributing traits and leaf rust resistance along with their parents and checks indicated that genetic material in the present investigation possessed sufficient variability which provides basis for selection by breeder. Moderate to high estimates of PCV and GCV obtained for yield per plant, yield per meter row and leaf rust resistance indicated a good deal of variability for these characters signifying the effectiveness of selection of desirable types for improvement of these traits. High heritability assisted with high genetic advance as per cent of mean was observed for plant height, days to fifty percent flowering, yield per plant, yield per meter row and leaf rust resistance. Hence, simple selection based on phenotypic performance of these traits would be more effective. Present investigation suggests that selection for the traits like days to fifty percent flowering, plant height and leaf rust resistance will be beneficial for improvement of yield parameters and leaf rust resistance in evolving potential genotypes in wheat.